Istanbul Policy Center - article Editorial (Сравнительная политика)
Istanbul Policy Center is an independent policy research institute with global outreach.Our mission is to foster academic research in social sciences and its application to policy making. We are fi rmly committed to providing decision makers, opinion leaders, academics, and the general public with innovative and objective analyses in key domestic and foreign policy issues.